2023
DOI: 10.1021/acsaelm.3c00373
|View full text |Cite
|
Sign up to set email alerts
|

Facile Direct Printing of DPP-Based Polymers for Organic Field-Effect Transistors and Logic Gates

Abstract: Polymer semiconductors having solubility in organic solvents can enable facile, low-cost, and large-area solution processes to fabricate electronic devices with various applications. However, it has been a challenge to build complicated circuits by using them due to device-to-device variation. In this study, we designed a diketopyrrolopyrrole (DPP)-based polymer with long and branched alkyl side chains to improve the solubility of DPP polymers. While the long and branched side chains are introduced to the DPP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…5,7-bis(trimethylstannyl)-2,3-dihydrothieno [3,4-b][1,4]dioxine (EDOT-SnBu 3 ) was acquired from SunaTech (Suzhou, China). Both DPP-Br-C8C10 and DPP-Br-C10C12 were prepared from DPP units via alkylation and bromination reactions [49,50].…”
Section: Methodsmentioning
confidence: 99%
“…5,7-bis(trimethylstannyl)-2,3-dihydrothieno [3,4-b][1,4]dioxine (EDOT-SnBu 3 ) was acquired from SunaTech (Suzhou, China). Both DPP-Br-C8C10 and DPP-Br-C10C12 were prepared from DPP units via alkylation and bromination reactions [49,50].…”
Section: Methodsmentioning
confidence: 99%
“…Simultaneously, the DPP itself is an electron acceptor unit, which can further significantly improve the carrier mobility and device performance of the material through donor–acceptor interactions within the main chain [ 24 ]. Kim et al reported polymers based on the composition of DPP and thieno[3,2-b]thiophene, which enabled direct line printing transistors [ 25 ]. Similarly, Tsuyoshi et al also optimized the performance of devices by adjusting the molecular weight of a DPP and thiophene based polymer [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sona et al prepared PTDPP-TT materials and revealed an average mobility of 0.90 cm 2 V −1 s −1 [25]. These structural analogs are also used in solution-processed integrated electronic components due to their excellent solubility and show a mobility of 0.1 cm 2 V −1 s −1 and low hysteresis [26]. The introduction of a double bond between thiophene and thiophene facilitates the formation of conformational locks, thus further ensuring the coplanarity of the material.…”
Section: Introductionmentioning
confidence: 99%